The effect of anthocyanins supplementation on liver enzymes among patients with metabolic disorders: A systematic review and meta‐analysis of randomized clinical trials. (12th September 2021) - Zhou, Fengling; She, Wei; He, Lin; Zhu, Jiuqun; Gu, Lu
Abstract : The present study aims to summarize and quantitatively examine the available evidence on the effectiveness of anthocyanin supplementation on liver enzymes among patients with metabolic disorders, by employing a systematic review and meta‐analytic approach. Online databases including PubMed/Medline, Scopus, ISI Web of Science, and Cochrane Library were searched up to June 2020 for randomized controlled trials (RCTs) that examined the effect of anthocyanin supplementation on serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) among patients with metabolic disorders. To estimate the overall effect of anthocyanin supplementation, we employed the random‐effects model. In total, 12 RCTs were included in the systematic review. Pooled analysis did not show any significant changes in ALT (WMD: ‐0.92 U/L, 95% CI: − 4.19 to 2.35, p = .58; I 2 = 91.3%) and AST (WMD: −1.22 U/L, 95% CI: −3.43 to 0.99, p = .28; I 2 = 87.0) concentrations after supplementation with anthocyanin. The dose and duration of supplementation were the potential sources of heterogeneity among most of the trials. However, subgroup analysis showed that the effect is not statistically significant in all subgroups. Overall, in our study, anthocyanin does not have any effect on liver enzyme levels significantly. However, future high‐quality studies are still needed to confirm the results.